ZnIIBisterpyridine Metallopolymers: Improved Processability by the Introduction of Polymeric Side Chains. Issue 10 (2nd April 2013) - Wild, Andreas; Teichler, Anke; von der Ehe, Christian; Winter, Andreas; Hager, Martin D.; Yao, Bing; Zhang, Baohua; Xie, Zhiyuan; Wong, Wai‐Yeung; Schubert, Ulrich S.
Abstract Introducing well‐defined polymeric side chains to bisterpyridine coordination polymers enables the synthesis of materials with tailor‐made optical and mechanical properties. The polymers are introduced either by a copper‐catalyzed azide–alkyne cycloaddition (grafting‐onto) or an atom transfer radical polymerization (polymerization‐from) method. The resulting metallopolymers exhibit improved solubility in common organic solvents and can, therefore, be inkjet‐printed from chlorinated benzene solutions. The photophysical properties of the so‐produced homogeneous films are investigated and a proof‐of‐principle polymer light‐emitting device can be constructed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>